SANKSI TINDAKAN SEBAGAI SARANA ALTERNATIF PENANGGULANGAN KEJAHATAN PSIKOTROPIKA BAGI PECANDU DAN PELAKU ANAK DALAM PERSPEKTIF HUKUM PIDANA - Anggoro Wicaksono Wicaksono; Alvi Syahrin Syahrin; Budiman Ginting Ginting; Marlina Marlina (USU LAW JOURNAL, 2015)
ABSTRACT One problem arising from the use of narcotics and psychotropic substances by children addict. Children are protected by Law No. 3 of 1997 on the Juvenile Court in which action alternative sanction can be applied to children through the law. The question arises what if the addict child which distribute narcotics and psychotropic substances, whether punitive action is done through sanctions. These questions arise because the child is protected by law while the addict must be severely punished by law. Criminal offenses committed by a child should be seen and understood as a social phenomenon, meaning that one should not give a bad stigma or sign that the child is evil for committing a crime, but we must understand and give attention and affection to them. Judicial approach to the child who committed the crime should be closer to the approach persuasive, educational, psychological, which means as far as possible to avoid legal proceedings solely punitive, dropping mental (mental degradation) and face stigmatization that can inhibit the growth and maturity of a reasonable of children.